Determinant of sharia rural bank profitability: Do size and location matter? - Agus Widarjono (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2024)
This research analyzes the influence of bank fundamentals, bank size, location, and macroeconomic variables on the profitability of Sharia Rural Banks (SRBs) in Indonesia. Our study investigates 90 banks located on the island of Java. The research period is 2018-2021, using quarterly data. The dynamic panel regression is employed with a GMM method. The findings indicate that strong bank fundamentals, as indicated by large assets, high CAR, and high efficiency, have a positive effect on profitability. There are two other interesting findings in this study. First, large SRBs encourage high profitability. Second, locations with high economic growth and high religiosity foster profitability. Some policy implications can be drawn from our findings. First, SRB must have sufficient capital and a high level of efficiency to increase profitability. Second, a large SRB is the best choice for an SRB to have sound financial performance. Third, SBRs must intensively introduce Sharia banking products to the public to increase their performance because religiosity is an important factor in determining profitability.